An Analysis of Criminal Responsibility of Health Facility to Refuse Of Services for Emergency Patients - Nursya Nursya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Health facility leaders can be threatened with punishment if there is a refusal emergency patient has been formulated by the Health Act 2009. The Health Act has formulated criminal threats since 2009. is cumulative in the form of imprisonment and fines for the state, which are pretty heavy. As for victims who may experience disability or death, their rights are not clearly stated by Law; although there is room in the Criminal Procedure Code, it is not easy. Efforts to find justice quickly can also be found through the paradigm of restorative justice or the authority of judges with rechtvinding. In the future, there needs to be changes or revisions to the health law regarding the criminal responsibility of leaders so that a sense of justice is obtained for both parties.